Postprandial walking but not consumption of alcoholic digestifs or espresso accelerates gastric emptying in healthy volunteers - Franke, Andreas; Harder, Hermann; Orth, Anna Katharina; Zitzmann, Sabine; Singer, Manfred V. (Journal of gastrointestinal and liver diseases, 2008)
Background: Postprandial consumption of alcoholic beverages with high ethanol concentration (so-called digestifs) is a widespread custom to alleviate dyspeptic symptoms after comprehensive meals. Alcoholic beverages preprandially ingested inhibit gastric emptying rate of solid meals. However, the effect of a postprandial intake has never been studied in a controlled manner.Methods: In 10 healthy male subjects gastric emptying was repeatedly studied by ultrasonography after the intake of a 576 kcal meal. Immediately after the meal subjects received in a randomized order 40 ml of the following liquids: brandy, herb flavored liqueur, Williams pear brandy, aquavit (each 40 % (v/v) ethanol concentration), espresso, water, 40% (v/v) ethanol and 70% (w/v) glucose. Postprandial satiety, fullness and bloating were determined on a visual analogue scale every 10 minutes. On another occasion subjects received 40 ml of water and walked afterwards slowly (4 km/h) on a treadmill. - Results: Gastric half emptying time (t 1/2) of the meal with water was 123ą5 min, while with brandy (119ą9 min), herb flavored liqueur (123ą10 min), aquavit (125ą9 min), Williams pear brandy (126ą6 min) or espresso (125ą9 min) t(1/2) it was not significantly different. Postprandial walking accelerated t(1/2) significantly (107ą5 min, p=0.02). Dyspeptic symptoms were unchanged. Blood ethanol concentrations were under the level of detection (< 5 mg/dl).Conclusions: Postprandial consumption of alcoholic digestifs did not affect gastric emptying rate of a solid meal nor postprandial dyspeptic complaints. However, postprandial walking accelerated gastric emptying of the meal but this had no effect on dyspeptic symptoms.